การศึกษาผลงานจิตรกรรมฝาผนังในพระอุโบสถวัดถ้ำตะโกพุทธโสภา อำเภอท่าวุ้ง จังหวัดลพบุรี STUDY OF MURAL PAINTINGS IN THE BUDDHIST TEMPLE WAT THAM TAKO BUDDHASOPA TAWUNG DISTRICT LOPBURI PROVINCE - อนุกูล จุติรัช (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2017)
บทคัดย่อ การศึกษาผลงานจิตรกรรมฝาผนังในพระอุโบสถวัดถ้ำตะโกพุทธโสภา อำเภอท่าวุ้ง จังหวัดลพบุรี มีวัตถุประสงค์เพื่อศึกษาวิเคราะห์ผลงานจิตรกรรมฝาผนังของวัดถ้ำตะโกพุทธโสภา ในประเด็น เรื่องราว ความเชื่อ จากจิตรกรรมฝาผนังที่ปรากฏ การจัดวางภาพ และตำแหน่งของภาพ เทคนิควิธีการสร้างงาน และอิทธิพลที่ได้รับจากศิลปะยุคอื่นๆ ผลการวิจัยพบว่าจิตรกรรมในพระอุโบสถของวัดถ้ำตะโกที่มีอายุในสมัยต้นรัชกาลที่ 6 คือ พ.ศ. 2457 มีลักษณะเป็นจิตรกรรมแบบร่วมสมัย มีวิธีการเขียนภาพทัศนียภาพแบบตะวันตกผสมผสานกับการเขียนภาพแบบจิตรกรรม 2 มิติแบบไทย บางส่วนได้รับอิทธิพลจากศิลปะแบบจีน ภายในพระอุโบสถของวัดถ้ำตะโกมีการจัดวางภาพที่ไม่เป็นไปตามขนบประเพณีดั้งเดิมในสมัยรัตนโกสินทร์ตอนต้นที่เคยทำมา ภาพจิตรกรรมที่พบภายในพระอุโบสถของวัดถ้ำตะโกพุทธโสภา ทั้งหมดยังเป็นความเชื่อแบบดั้งเดิมของพุทธศาสนา ได้แก่ ภาพผจญมาร ภาพตอนดับขันธ์ ปรินิพาน ภาพเสด็จกลับจากดาวดึงส์ ภาพอสุภกรรมฐาน ภาพนรกภูมิ ภาพเทพชุมนุมเป็นต้น Abstract The study of mural painting in the chapel of Wat Tham Tako Buddhasopa, Buddhist Temple, in Thawung District, Lopburi Province aimed at studying and analyzing the painting works on the wall of Wat Tham Tako Buddhasopa in the aspects of story of faith embedded in mural painting, mural painting images arrangements, mural painting images positions, creating techniques for mural painting, and artistic influences derived from other eras. The findings revealed that the mural paintings on the wall in the chapel of Wat Tham Tako Buddhasopa were created in the early reign of King Rama VI in B.E. of 2457 (1914 A.D.). The mural paintings shared the art of contemporary works, showing the western ways of painting and scenery with a combination of Thai two-dimension mural paintings. In addition, parts of the mural paintings were influenced by Chinese Art. There were also mural painting images arrangements not in accordance with the tradition of the early Rattanakosin Kingdom which most paintings in the Thai chapels replicated. The mural paintings found in the chapel of Wat Tham Tako Buddhasopa depicted the Buddhist story of faith about Maravijaya, the Buddha’s Parinibbana (death), Buddha’s return from heaven day, Buddha Story Jataka and Peace Meditation True Relaxation, Mouth of Hell, and Deity gathering.